2014
DOI: 10.15346/hc.v1i1.2
|View full text |Cite
|
Sign up to set email alerts
|

Group Minds and the Case of Wikipedia

Abstract: Group-level cognitive states are widely observed in human social systems, but their discussion is often ruled out a priori in quantitative approaches. In this paper, we show how reference to the irreducible mental states and psychological dynamics of a group is necessary to make sense of large scale social phenomena. We introduce the problem of mental boundaries by reference to a classic problem in the evolution of cooperation. We then provide an explicit quantitative example drawn from ongoing work on coopera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…Wikipedia's norms for editor interaction are "highly conservative" and long-lived in comparison to most other online communities [35]. Today, much authority on the site remains grounded in a small network of policies shaped early in the site's history [8], written originally in response to a period of heavy growth and necessary crowd control. Some of the earliest policies, like Notability (N), Verifiability (V), and No Original Research (NOR, see Figure 1) originated many years ago but continue to dominate editorial discussion and drive group decision-making, while newer rules remain comparatively obscure [27].…”
Section: Background On Wikipediamentioning
confidence: 99%
“…Wikipedia's norms for editor interaction are "highly conservative" and long-lived in comparison to most other online communities [35]. Today, much authority on the site remains grounded in a small network of policies shaped early in the site's history [8], written originally in response to a period of heavy growth and necessary crowd control. Some of the earliest policies, like Notability (N), Verifiability (V), and No Original Research (NOR, see Figure 1) originated many years ago but continue to dominate editorial discussion and drive group decision-making, while newer rules remain comparatively obscure [27].…”
Section: Background On Wikipediamentioning
confidence: 99%
“…[68] constructed a game-theoretic model to back-infer the underlying beliefs and desires of the users from their behavior alone. In the spirit of earlier work in inductive game theory [70,71], our fundamental goal was to understand the cognitive complexity of the individuals, and how they reacted to the contexts in which they found themselves.…”
Section: Broken Windows and The Normative Pathwaymentioning
confidence: 99%
“…Ref. [68] found that norm-conformity accumulates faster when individuals interact (α driven towards one), suggesting that reputation drives learning. A "cheap-talk" result-norm-conformity is not affected by use of associated discussion pagesfurther complicates the analysis.…”
Section: Broken Windows and The Normative Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…We define a revert as an edit that takes the page to a previously-seen state (as detected by the MD5 page hash provided by the Wikipedia API), but exclude the relatively small number of cases where a user's revert only undoes work contributed by that user herself (i.e., we exclude self-reverts). More details on these methods, and additional robustness checks, are described in [16].…”
Section: Tracking Conflict Through Page Revertsmentioning
confidence: 99%